Pengaruh Media Pembelajaran Moodle Berbasis Youtube Terhadap Hasil Belajar Mahasiswa - Wahyuni, Arie; Hidayati, Destia Wahyu (Politeknik Indonusa Surakarta, 2021)
The purpose of this study was to determine the effect of youtube-based moodle learning media on student learning outcomes. This research method uses quasi-experimental. The results showed that there was an influence of youtube-based moodle learning media on student learning outcomes, this was indicated by the posttest results being higher than the pre-test results.